Quantifying Soil and Nutrients Losses under Different Soil Amendments and Cropping Systems on a Plinthic Vetic Lixisol in Ghana - Bigabwa, Janvier Bashagaluke (2019)
A thesis submitted to the Department of Crop and Soil Sciences, Faculty of Agriculture, College of Agriculture and Natural Resources, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana in partial fulfillment of the requirement for the award of degree of Doctor of Philosophy in Soil Science.